Association Between Cathepsin S, Cystatin C and High Sensitivity C-Reactive Protein (hsCRP) with Oxidized LDL (Ox-LDL) in Men with Central Obesity - Emmy F Harefa; Ilhamjaya Patellongi; Marita Kaniawati (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Inflammation is a central feature of the atherosclerotic process particularly in obesity. hsCRP, a marker of inflammation, may be directly involved in all phases of atheroslerosis by complement activation, apoptosis, vascular cell activation, monocyte recruitment, lipid accumulation and thrombosis. Inflammation has a causal relationship with cysteine proteases including cathepsin S. Therefore, cathepsin S is considered as a molecular link between obesity and atherosclerosis. An imbalance between elastolytic cysteine proteases, cathepsin S and its inhibitor, cystatin C, is involved in the pathogenesis of atherosclerosis. Some studies have shown that increased circulating levels of cathepsin S, hsCRP and cystatin C in inflammatory conditions contribute to atherosclerosis. This study was conducted to investigate the associations between ox-LDL and cathepsin S, and cystatin C and hsCRP in men with central obesity.METHODS: This was a cross-sectional study involving 71 male subjects with central obesity (waist circumference ≥90 cm), with no renal dysfunction, aged 30-60 years.RESULTS: Cathepsin S did not have a significant correlation with ox-LDL (r=0.158, p=0.096). ox-LDL had positive correlation with cystatin C (r=0.156; p=0.029) and hsCRP (r=0.204; p=0.045), and cathepsin S/cystatin C ratios (r=0.360; p=0.024) at level >91 U/L (median ox-LDL).CONCLUSIONS: There were associations between ox-LDL and cystatin C, hsCRP and cathepsin S/cystatin C ratios in men with central obesity.KEYWORDS: obesity, inflammation, atherosclerosis, hsCRP, cystatin C, cathepsin S, ox-LDL